2002
DOI: 10.1029/2001jb000377
|View full text |Cite
|
Sign up to set email alerts
|

Migration of seismicity and earthquake interactions monitored by GPS in SE Asia triple junction: Sulawesi, Indonesia

Abstract: Global Positioning System (GPS) measurements made in Sulawesi, Indonesia, from 1992 to 1999 detected coseismic and transient postseismic deformation related to the 1 January 1996, Mw = 7.9 earthquake on the North Sulawesi (Minahassa) trench. These motions are superimposed on the long‐term secular motion (40 mm/yr) of the left‐lateral Palu fault in central Sulawesi and continued for about 1.5–2 years. Following the earthquake, a string of earthquakes (of magnitude >6) migrated along the Minahassa trench, from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…Geological investigations, geomorphic and GPS observations (Socquet et al, ; Walpersdorf, Vigny, et al, ) confirmed that the PKF is a fast moving fault with a relatively low level of seismicity. Since 1 January 1996 when an earthquake sequence was initiated by the Mw 7.9 Tomini earthquake along the Minahassa thrust (Vigny et al, ), the seismicity near the PKF began to be active gradually.…”
Section: Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Geological investigations, geomorphic and GPS observations (Socquet et al, ; Walpersdorf, Vigny, et al, ) confirmed that the PKF is a fast moving fault with a relatively low level of seismicity. Since 1 January 1996 when an earthquake sequence was initiated by the Mw 7.9 Tomini earthquake along the Minahassa thrust (Vigny et al, ), the seismicity near the PKF began to be active gradually.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Although the triple junction zone is highly seismically active, the seismic records show a low level of shallow seismicity in central Sulawesi (Bellier et al, ; McCaffrey & Sutardjo, ). Contrary to the low seismicity, geomorphic and tectonic studies gave a high long‐term slip rate, up to ~40 mm/year, on the PKF (Bellier et al, ; Stevens et al, ; Vigny et al, ; Walpersdorf, Rangin, et al, ; Walpersdorf, Vigny, et al, ). The present‐day GPS measurements provided a similar estimate of slip rate, but the motion is distributed on four parallel strands across a broad zone 50 km to the east (Socquet et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The inter-seismic stress accumulation rate distribution along the entire Palu-Koro fault remains unclear. However, Vigny et al (2002) calculated the maximum principal horizontal strain rate of about 311 and -291 nanostrain/a oriented 113°(±2°) using the geodetic data obtained on the Palu-Koro fault in the Palu basin. Based on this estimation, we could deduce a maximum principal stress rate of 3.11 and -2.91 kPa/a on the Palu-Koro fault assuming an elastic modulus of 1.0×10 10 Pa. By integrating a roughly estimated tectonic loading Coulomb stress rate of approximately 1.0 kPa/a (approximately one third of the maximum principal stress rate), the promoted ΔCFS (51 kPa) was consistent with tectonic loading over approximately 51 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sulawesi Island moves northwestward following clockwise rotation about 4°/Ma. In comparison, the Australian plate drifts northward, the Philippine Sea plate moves westward, and Sunda plate blocks the west (Vigny et al, 2002;Socquet et al, 2006). The Celebes Sea floor subducts the northern region beneath Sulawesi, and the Minahassa trench accommodates the northwestward movements of the Sula block relative to the Sunda plate (Socquet et al, 2006).…”
Section: Geological Settingmentioning
confidence: 99%
“…A number of crustal blocks take part in this rotation, the Makassar block in SW Sulawesi, the North Sula block, the Manado block and the East Sula block in NE Sulawesi (Figure 7c). Walpersdorf et al [1998] indicate a location of plate intersection in the southern Molucca Sea (represented by a star in Figure 7c), although the convergence area has a 500 km diameter in total [ Vigny et al , 2002]. …”
Section: Tsunami Hazard Methodology and Scenario Descriptionsmentioning
confidence: 99%